Case Report: Pneumonia Like Mass with Spontaneous Resolution - Aisyah Ayu Safitri; Muhammad Fahmi Alatas (Jurnal Respirologi Indonesia, 2023)
Background: Pneumonia can easily mimic malignancies. Pulmonary nodule finding raise concern for lung cancer. A single lung opacity less than 3 centimetres in diameter is referred to as a solitary pulmonary nodule (SPN). These nodules sometimes incidentally discovered during routine computed tomography (CT) scan of the chest in relatively asymptomatic patients. We present unusual case of pneumonia like mass with spontaneous resolution.Case: Woman, 38-year-old, with solitary pulmonary nodule which was found accidentally in the left lung upper lobe, without any respiratory symptoms in June 2021. In August 2021, a chest CT scan was done for evaluating and the solitary nodule of the left lung upper lobe had resolved spontaneously without any treatment. The patient was prepared for diagnostic bronchoscopy at Persahabatan Hospital with the findings of normal bronchi and the branches. A bronchial washing was performed on the left B1+2 segment and cytology, fungal, microorganism and molecular tuberculosis examination were performed.Discussion: Pulmonary solitary nodule in left lung upper lobe in the beginning and spontaneous resolution after 2 months evaluation without any specific treatment, consider period of pneumonia. Whenever a patient is found to have an SPN, it is essential to determine the patient’s risk for malignancy. It is important to consider any pulmonary nodule to be malignant or not, and how it presents on CT Imaging.Conclusion: Pulmonary nodule may be found during pneumonia and may resolve spontaneously. The possibility of malignancy must still be considered. Awareness of condition from the history is important to help reassure patient about the disease even before diagnostic procedure was made.